Estratégias para o estudo de marcadores moleculares da fertilidade em modelos animais: perfil metabolômico do plasma seminal em touros e expressão da integrina subunidade beta 5 no espermatozoide, oócito e embrião bovino - Velho, Ana Luiza Malhado Cazaux de Souza (2017)
Metabolites and proteins including integrins are important in the reproductive physiology of animals and humans. However, seminal plasma metabolites that are associated with bull fertility are still unknown and the possible roles of the integrin subunit beta 5 (ITGβ5) in fertilization and embryonic development of bovine are not yet known. Therefore, the objectives of the present study were (1) to determine comprehensive metabolome of seminal plasma from Holstein bulls with differing fertility scores, and (2) to ascertain potential metabolites as biomarkers associated with bull fertility, (3) to evaluate expression of ITGβ5 in sperm, oocytes and early bovine embryos, and (4) to ascertain the evolutionary conservation of ITGβ5. In the study 1, chromatography-mass spectrometry (GC-MS) was employed to determine seminal plasma metabolome from 16 Holstein bulls with two fertility scores. Soon after, data were evaluated using multivariate and univariate analyses. Bioinformatics analyzes were performed in order to identify metabolic pathways associated with bull’s seminal plasma metabolites. Our results showed that 63 metabolites were identified in bull seminal plasma. Fructose was the most abundant metabolite detected followed by citric acid, lactic acid, urea, and phosphoric acid. Androstenedione, 4-ketoglucose, D-xylofuranose, 2-oxoglutaric acid and erythronic acid were the least predominant metabolites found in bull’s seminal fluid. PLS-DA showed a distinct separation between high and low fertility bulls as regard to scores plot. Metabolites with the greatest VIP score (VIP > 2) were 2-oxoglutaric acid and fructose. Heat-map analysis based on VIP score and univariate analysis indicated that 2-oxoglutaric acid was less (P = 0.02) and fructose was significantly greater (P = 0.02) in high-fertility bulls as compared to low-fertility bulls. To the best of our knowledge the current study is the first to identify the comprehensive metabolomic profiling of bull seminal plasma with differing fertility score and to present the potential of metabolites such as 2-oxoglutaric acid and fructose as biomarkers of bull fertility using GC-MS. In the study 2, expression levels of ITGβ5 protein in bull sperm were evaluated by western blotting. Real time-qPCR was carried out to evaluate the expression levels of ITGβ5 transcripts in oocytes and embryos from bovine species. In addition, bioinformatic tools were performed to determine to evolutionary conservation of ITGβ5 across species. Western blotting results showed the presence of ITGβ5 on bull spermatozoa. Moreover, RT-qPCR results demonstrated that ITGβ5 is present in bovine oocytes and that ITGβ5 levels were significantly higher in 2-cell embryos and 8-16 cell embryos. Bioinformatics analyses showed that ITGβ5 is conserved across species. Therefore, our results showed the presence of ITGβ5 in spermatozoa as well as oocytes and embryos in early stages of development, suggesting an important role of ITGβ5 upon fecundation and early embryo development in the bovine species.